2021
DOI: 10.1016/j.jamda.2020.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medication Classes and the Risk of Dementia: A Systematic Review and Network Meta-Analysis

Abstract: Objectives: To systematically review and synthesize the evidence on differential associations between antihypertensive medication (AHM) classes and the risk of incident dementia. Design: Systematic review and random effects frequentist network meta-analysis. Embase, MEDLINE, and the Cochrane library were searched from origin to December 2019. Setting and participants: Randomized controlled trials (RCTs) and prospective cohort studies that compared associations of different AHM classes with incident all-cause d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
1
37
1
Order By: Relevance
“…Our randomised controlled trial does not support evidence from observational studies and a recent systematic review 29 that ARAs might offer preferential benefit over other forms of hypertension treatment regarding the incidence and progression of Alzheimer's disease. Other meta-analyses conclude that there are no such hypertension treatment differences over dementia incidence, 2 , 9 , 10 although those findings and others agree that hypertension management is protective.…”
Section: Discussioncontrasting
confidence: 83%
“…Our randomised controlled trial does not support evidence from observational studies and a recent systematic review 29 that ARAs might offer preferential benefit over other forms of hypertension treatment regarding the incidence and progression of Alzheimer's disease. Other meta-analyses conclude that there are no such hypertension treatment differences over dementia incidence, 2 , 9 , 10 although those findings and others agree that hypertension management is protective.…”
Section: Discussioncontrasting
confidence: 83%
“…Studies suggest that reducing BP (variability), influencing the renin-angiotensin system, and/or modulating intracellular calcium homeostasis, may protect against neural damage caused by vascular changes, increased blood-brain barrier permeability, inflammation, or ischemia, potentially through specific AHM class effects. [39][40][41][42][43][44] However, observational biases may also play a role. [39][40][41][42][43][44] Next to gold-standard neuropathological data, in vivo ADNCrelated biomarkers obtained from imaging and cerebrospinal fluid (CSF) may provide valuable context, because they allow investigating the relation between BP and ADNC during life, before the effects of old age and dementia.…”
Section: Literature Comparisonmentioning
confidence: 99%
“…Although previous studies have often shown inconsistent results, CCB and ARB likely had larger benefits than other antihypertensive drug classes on prevention of cognitive decline in meta-analysis of RCT and prospective cohort studies. 98 100 …”
Section: Introductionmentioning
confidence: 99%